The role of long-term contracting in business lending - Phoebe Tian (Bank of Canada, 2024)
This paper examines inefficiencies arising from a lack of long-term contracting in small business lending in China. I develop and estimate a dynamic model where firms repeatedly interact with the same lender. All loans are short-term. Collateral can be used to deter a strategic default by a firm, but the lender cannot recover the full value of the collateral in the case of a default. The endogenous contract terms-including interest rates, loan size and collateral-reflect a firm's probability of default in equilibrium. Learning drives the dynamics of contract terms because a firm's profitability type is unknown. Long-term contracts improve welfare mainly by mitigating the incentives for a firm to default.
Keywords: D83; D86; G21; L14; L26; 330; Financial Institutions